Nutritional and Physicochemical Quality of Vacuum-Fried Mango Chips Is Affected by Ripening Stage, Frying Temperature, and Time - Ayustaningwarno, Fitriyono; van Ginkel, Elise; Vitorino, Joana; Dekker, Matthijs; Fogliano, Vincenzo; Verkerk, Ruud (Frontiers in Nutrition, 2020)
For the production of healthier fruit snacks, vacuum frying is a promising alternative for atmospheric frying, to reduce the oil content, while maintaining a high nutritional quality. This paper evaluates the effect of ripening stages, frying temperature and time on the quality of vacuum fried mango. Unripe mango was dehydrated faster than ripe mango and had a higher hardness after frying at 110 and 120 °C. Fat content in fried ripe mango was higher. Total ascorbic acid and β-carotene in both ripening stages was not different, but after frying total ascorbic acid in unripe mango remains higher. A novel image analysis was applied to quantify the color distribution of fried mango. Color changes of unripe mango was more susceptible to temperature and time. Considering all quality parameters, vacuum frying of unripe mango at the optimal condition of 100 oC for 20 minutes is preferred for producing high quality healthier fruit snacks.